Amelioration of age‐related brain function decline by Bruton's tyrosine kinase inhibition. Issue 1 (17th November 2019) - Ekpenyong‐Akiba, Akang E.; Poblocka, Marta; Althubiti, Mohammad; Rada, Miran; Jurk, Diana; Germano, Sandra; Kocsis‐Fodor, Gabriella; Shi, Yu; Canales, Juan J.; Macip, Salvador
Abstract: One of the hallmarks of aging is the progressive accumulation of senescent cells in organisms, which has been proposed to be a contributing factor to age‐dependent organ dysfunction. We recently reported that Bruton's tyrosine kinase (BTK) is an upstream component of the p53 responses to DNA damage. BTK binds to and phosphorylates p53 and MDM2, which results in increased p53 activity. Consistent with this, blocking BTK impairs p53‐induced senescence. This suggests that sustained BTK inhibition could have an effect on organismal aging by reducing the presence of senescent cells in tissues. Here, we show that ibrutinib, a clinically approved covalent inhibitor of BTK, prolonged the maximum lifespan of a Zmpste24 −/− progeroid mice, which also showed a reduction in general age‐related fitness loss. Importantly, we found that certain brain functions were preserved, as seen by reduced anxiety‐like behaviour and better long‐term spatial memory. This was concomitant to a decrease in the expression of specific markers of senescence in the brain, which confirms a lower accumulation of senescent cells after BTK inhibition. Our data show that blocking BTK has a modest increase in lifespan in Zmpste24 −/− mice and protects them from a decline in brain performance. This suggests that specific inhibitors could be used in humans to treat progeroid syndromes and prevent the age‐related degeneration of organs such as the brain. Abstract : We showed that blocking Bruton's tyrosine kinase (BTK) dampens p53 activity and the induction of senescence in vitro. Here, we show that BTK inhibitors increase maximum lifespan and healthspan of progeroid mice. Moreover, they prevent the deterioration of certain cognitive functions and reduce the accumulation of senescent cells in the brain. This suggests that clinically available BTK inhibitors could ameliorate some features of ageing in susceptible patients.